2017
DOI: 10.1039/c7nr04697a
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ferrocenylsilane) electrolytes as a gold nanoparticle foundry: “two-in-one” redox synthesis and electrosteric stabilization, and sensing applications

Abstract: Gold nanoparticles (AuNPs) coated with responsive polymers gained considerable interest due to their controllable size, good stability, and fast environmental response suitable for biological applications and sensing. Here we report on a simple and efficient method for the synthesis of stable and redox responsive AuNPs using organometallic polyelectrolytes in aqueous solutions of HAuCl. In the redox reaction, positively or negatively charged poly(ferrocenylsilanes) (PFS/PFS) served as reducing agents, and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Our previous study on the rational design of amino acid‐derived biodots has revealed that serine (Ser) and threonine (Thr) dots possess inherent biocompatibility with high fluorescence quantum yields (QYs) . Polymers have been used as stabilizers or shape‐controlling agents in nanoparticle synthesis . In this work, we investigate the effect of differently charged polymers on the properties of the resulted biodots.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study on the rational design of amino acid‐derived biodots has revealed that serine (Ser) and threonine (Thr) dots possess inherent biocompatibility with high fluorescence quantum yields (QYs) . Polymers have been used as stabilizers or shape‐controlling agents in nanoparticle synthesis . In this work, we investigate the effect of differently charged polymers on the properties of the resulted biodots.…”
Section: Resultsmentioning
confidence: 99%
“…The redox activity of the PFS chain could be used to prepare metal nanoparticles in a facile in situ manner without using external reducing agents or organic solvents . The synthesis of NPs was carried out by immersion of a piece of hydrogel in a solution of metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…[120] Reproducedw ith permissionfrom Ref. [120].Copyright 2017, Royal SocietyofC hemistry. [121] Reproduced with permission from Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al reported the preparation of PFS-based polyelectrolytesf or the decoration of gold nanoparticles (PFS@AuNPs). [120] The PFS polyionsw eree ither positively or negativelyc harged, and used as polymer reducing ands tabilization reagents. The redox-responsiveness of the PFS immobilized at the surfaceo ft he AuNPs revealed localized surface plasmon resonance (SPR) nanostructures provided access to switchable color tuning ( Figure 6).…”
Section: Opticalapplications For Metallopolymersmentioning
confidence: 99%